SPHK1 regulates proliferation and survival responses in triplenegative breast cancer - Datta, A.; Loo, S.; Huang, B.; Wong, L.; Tan, S.; Tan, T.; Lee, S.; Thiery, J.; Lim, Y.; Yong, W.; Lam, Y.; Kumar, Alan Prem; et al. (Impact Journals LLC, 2014)
Triple-negative breast cancer (TNBC) is characterized by unique aggressive behavior and lack of targeted therapies. Among the various molecular subtypes of breast cancer, it was observed that TNBCs express elevated levels of sphingosine kinase 1 (SPHK1) compared to other breast tumor subtypes. High levels of SPHK1 gene expression correlated with poor overall and progression- free survival, as well as poor response to Doxorubicin-based treatment. Inhibition of SPHK1 was found to attenuate ERK1/2 and AKT signaling and reduce growth of TNBC cells in vitro and in a xenograft SCID mouse model. Moreover, SPHK1 inhibition by siRNA knockdown or treatment with SKI-5C sensitizes TNBCs to chemotherapeutic drugs. Our findings suggest that SPHK1 inhibition, which effectively counteracts oncogenic signaling through ERK1/2 and AKT pathways, is a potentially important anti-tumor strategy in TNBC. A combination of SPHK1 inhibitors with chemotherapeutic agents may be effective against this aggressive subtype of breast cancer.